2012
DOI: 10.1038/nm.2994
|View full text |Cite
|
Sign up to set email alerts
|

Protein typing of circulating microvesicles allows real-time monitoring of glioblastoma therapy

Abstract: Glioblastomas shed large quantities of small, membrane-bound microvesicles (MVs) into the circulation. While these hold promise as potential biomarkers of therapeutic response, their identification and quantitation remain challenging. Here, we describe a highly sensitive and rapid analytical technique for profiling circulating MVs directly from blood samples of glioblastoma patients. MVs, introduced onto a dedicated microfluidic chip, are labeled with target-specific magnetic nanoparticles and detected by a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
687
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 658 publications
(722 citation statements)
references
References 37 publications
14
687
0
5
Order By: Relevance
“…Alternatively, to overcome these issues, beads can be used to specifically capture MVs. For example, micro-NMR technology using tetrazine-labelled magnetic nanoparticle-captured EVs has also been successfully used to detect tumoural EGFRv3+ EVs in glioblastoma patients [37]. In agreement with these results, the present study demonstrates the ability of antibody-coated magnetic beads to specifically isolate MVs of a definite cellular origin independently of the coating process.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Alternatively, to overcome these issues, beads can be used to specifically capture MVs. For example, micro-NMR technology using tetrazine-labelled magnetic nanoparticle-captured EVs has also been successfully used to detect tumoural EGFRv3+ EVs in glioblastoma patients [37]. In agreement with these results, the present study demonstrates the ability of antibody-coated magnetic beads to specifically isolate MVs of a definite cellular origin independently of the coating process.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, in our series of septic patients, we found that survivors had significantly higher MV-PGC values both at inclusion and 24 h later than healthy controls (Figure 5(a)) and nonsurvivors (3.1 [1.7–18] vs 1.4 [0.8–3.0] A 405nm  × 10 −3 /min, p  = 0.02, H0; 5.2 [2.2–16] vs 1.4 [1–1.6] A 405nm × 10 −3 /min, p  = 0.004, H24). As expected, PAI-1 activity was significantly lower at admission in the patients who survived (S) compared with those who died (NS) (median [interquartile range]; 3 [237] vs 43 [34–55] a.u. (arbitrary units)/mL, p  = 0.008, Figure 5(b)).…”
Section: Resultssupporting
confidence: 60%
“…Interestingly, one other type of microfluidic chip was recently reported for MV characterization in biological fluids based on labelling with magnetic nanoparticles and miniaturized nuclear magnetic resonance detection 7 . Although it was shown to be capable of discriminating different types of MVs with high sensitivity, it does not feature independent size and concentration measurements.…”
Section: Resultsmentioning
confidence: 99%
“…tumour growth and metastasis, is a topic that receives a lot of attention nowadays [1][2][3][4][5][6] . The size, origin and concentration of cell-derived MVs could entail clinically relevant signatures with diagnostic and prognostic value 2,5,7 . Thus, substantial efforts have gone into evaluating and developing techniques suitable for submicron MV characterization in terms of specificity, size and concentration 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Shao et al used μ NMR to detect target-specific magnetic nanoparticles after on-chip isolation [106]. …”
Section: Microfluidics-based Detection and Analysis Systemsmentioning
confidence: 99%